Law and Conflict Resolution in Kashmir - Balcerowicz, Piotr; Kuszewska, Agnieszka (Taylor & Francis, 2022)
More than seven decades of Kashmir dispute brought numerous plans, formulas, and resolution initiatives proposed and negotiated both multilaterally and bilaterally. The urge to resolve the conflict constructively is repeatedly underscored by decision-makers in India and Pakistan and, occasionally, by global leaders and organizations, but they remained unfulfilled declarations. Since the first Kashmir war in the aftermath of the partition of the subcontinent, the agenda for resolution (in accordance with their respective goals and objectives) was accompanied by mutual Indo-Pakistani accusations of bad intentions, dishonesty and unwillingness to genuinely engage in peace building initiatives. Conspicuously, both Indian and Pakistani establishments intentional exacerbate bilateral tensions with disregard for common interests of Indians, Pakistanis and the residents of Kashmir. This chapter presents certain noteworthy resolution attempts and plans put forward by international actors as well as Indian, Pakistani and Kashmiri stakeholders, non-governmental organisations, civil society, political and human rights activists, etc.